Regional Trade Agreements and the Environment Developments in 2010 - George, Clive (OECD Trade and Environment Working Papers, 2011)
This report provides an update on recent developments in the field of Regional Trade Agreements and the environment. Issues arising in the implementation of RTAs with environmental considerations are examined as well as experience in assessing their environmental impacts. It is the fourth update prepared under the aegis of the Joint Working Party on Trade and Environment. The report covers developments over the period from late 2009 to December 2010 and is based on publicly available information